Comparison of Skin Permeation and Putative Anti-Inflammatory Activity of Commercially Available Topical Products Containing Ibuprofen and Diclofenac - Pradal, Julie (J Pain Res, 2020)
PURPOSE: The therapeutic effect of topical nonsteroidal anti-inflammatory drugs (NSAIDs) depends on the drug’s ability to penetrate and permeate the skin and subsequently inhibit cyclo-oxygenase (COX) isoforms responsible for pain and inflammation. Most commercially available topical NSAID formulations are clinically effective, but direct comparisons of anti-inflammatory activity including both skin absorption and inhibitory potency are lacking. This study examined the skin absorption of representative commercially available topical diclofenac- and ibuprofen-based formulations along with published potency values to determine formulations with superior anti-inflammatory activity. MATERIALS AND METHODS: Cumulative absorption and flux profiles of 12 commercially available topical NSAIDs (6 diclofenac-based and 6 ibuprofen-based) were evaluated in vitro using human skin in static Franz diffusion cells. Each formulation was applied as a single dose. In vitro permeation parameters and published COX-2 inhibition values were used to calculate a modified index of topical anti-inflammatory activity (mITAA). RESULTS: All diclofenac and ibuprofen formulations permeated human skin in vitro. The rate and degree of absorption differed between diclofenac and ibuprofen formulations and between formulations of the same drug. NSAID concentration within a product was not solely responsible for the permeation flux or degree of absorption. Ibuprofen formulations permeated the skin more rapidly and to a greater degree than diclofenac, but calculated mITAAs were higher for diclofenac. CONCLUSION: Diclofenac exhibited superior anti-inflammatory activity as measured by the index. Differences beyond drug concentration, including excipients, drug salt form, and dosage form, contribute to differences in absorption and thus in anti-inflammatory activity. Both absorption and COX-2 inhibition potency are important for anti-inflammatory activity, but their priority depends upon the products being compared—with the same NSAID, absorption determines superiority; with different NSAIDs, superiority is determined by the balance between absorption and COX-2 potency. These findings should be considered when selecting a topical NSAID for treating patient pain and inflammation.